Polycyclic aromatic hydrocarbons in surface seawater at the southern Okhotsk Sea, 2017–2022 - Rodrigo Mundo; Tetsuya Matsunaka; Mutsuo Inoue; Saki Tanaka; Mone Ozawa; Yukiko Taniuchi; Takuya Nakanowatari; Hiromi Kasai; Hideki Kaeriyama; Shizuho Miki; Yuliya Koudryashova; Tatiana Chizhova; et al. (Marine Pollution Bulletin, 2026)

Comprehensive genomic analysis of five kindreds with multiple childhood leukemias: importance of individual functional analysis for rare ETV6 germline variants - Ai Yamada; Shun Nagasawa; Midori Nakagawa; Sachiyo Kamimura; Nami Inoue; Hiroyoshi Watanabe; Masatoshi Takagi; Yuhki Koga; Dai Keino; Hideki Nakayama; Jun Yoshimura; Koichiro Doi; et al. (Human Cell, 2026)
Germline variants in leukemia predisposition genes are increasingly detected in pediatric patients. Nevertheless, the rare variants identified in diagnostic samples may be misinterpreted without variant-level functional evaluation and cautious clinical interpretation. Whole-exome sequencing was performed on 28 individuals from five kindreds in which at least two children developed acute leukemia. Results identified a rare ETV6 variant, c.604C > G (p.Arg202Gly), in monozygotic twins with ETV6::RUNX1 -positive B-cell precursor acute lymphoblastic leukemia. To support variant interpretation, HeLa-cell populations stably expressing FLAG-tagged wild-type ETV6 and p.Arg202Gly and the known loss-of-function control p.Pro214Leu were established. Subcellular localization was assessed via immunofluorescence microscopy with quantitative scoring. Transcriptional repression was evaluated using luciferase reporter assays driven by ETV6 target promoters ( MMP 3 and PF4 ). p.Arg202Gly predominantly showed nuclear localization comparable to WT, whereas p.Pro214Leu was enriched in the cytoplasm. In the reporter assays, similar to WT, p.Arg202Gly retained repression activity. Meanwhile, p.Pro214Leu failed to repress both reporters. The in-silico prediction of nuclear export sequences suggested an additional export signal in p.Pro214Leu, but not in p.Arg202Gly. Collectively, these findings indicate that p.Arg202Gly behaves as WT-like in the assays performed and do not support a loss-of-function effect. Our study emphasizes the importance of variant-level functional assessment for rare ETV6 variants to inform clinical interpretation and avoid overestimation of pathogenicity.

Development of 5-year risk prediction models for incident dementia and mortality in a community-dwelling older Japanese population: The Japan Prospective Studies Collaboration for Aging and Dementia (JPSC‐AD) - Xiangyin Meng; Takanori Honda; Tomoyuki Ohara; Yoshihiko Furuta; Mao Shibata; Jun Hata; Yasuyuki Taki; Tatsuya Mikami; Tetsuya Maeda; Kenjiro Ono; Masaru Mimura; Ritsuko Hanajima; et al. (GeroScience, 2026)
Improving cognitively healthy survival is important for achieving healthy aging. Therefore, it would be valuable to estimate the future risk of either incident dementia or death in community-dwelling older adults. This study aimed to develop a set of risk prediction models for either incident dementia or death that can be applied according to data availability across diverse clinical settings, using longitudinal data from community-dwelling older Japanese adults. A total of 8,334 participants aged ≥65 years were prospectively followed up from 2016 to 2023. Logistic regression was used to develop multivariable prediction models. The developed models were translated into simplified scoring systems based on the β coefficients. The discrimination abilities of the models were assessed by C-statistics, and the calibration was assessed by calibration plots. During the follow-up period, 1,151 participants developed either dementia or death. In the multivariable model using potential predictors commonly available in the primary care setting, age, male sex, formal education ≤9 years, diabetes mellitus, use of lipid-lowering agents, leanness, history of stroke, history of heart disease, history of respiratory disease, history of cancer, current smoking, no regular exercise habit, and low frequency of social interactions were selected as predictors. Adding cognitive status, depressive symptoms, apolipoprotein E-ε4 carrier status, and brain MRI markers to the model further enhanced its predictive performance. The developed models and simplified scores showed good discrimination and calibration. Risk stratification with our models may be useful for assessing the risks of incident dementia and death and, consequently, for prolonging cognitively healthy survival.

Opposite latitudinal biodiversity gradient in the open ocean generated by transition zones: Insights from fish distribution in the Northwest Pacific - Yuan Lin; Zeshu Yu; Sk Istiaque Ahmed; Xueding Wang; Tomihiko Higuchi; Itsuka Yabe; Marty Kwok-Shing Wong; Sachihiko Itoh; Eisuke Tsutsumi; Hiroaki Saito; Kosei Komatsu; Atsushi Tsuda; et al. (Progress in Oceanography, 2026)

Patterns in marine surface fish biodiversity and community composition detected by different eDNA metabarcoding sampling methods - Sk Istiaque Ahmed; Zeshu Yu; Tomihiko Higuchi; Jun Inoue; Marty Kwok-Shing Wong; Xueding Wang; Yuan Lin; Sachihiko Itoh; Kosei Komatsu; Eisuke Tsutsumi; Hideki Fukuda; Susumu Hyodo; et al. (Journal of Oceanography, 2026)
Understanding marine surface fish diversity is crucial for ecosystem management. However, the traditional sampling methods are often invasive, costly, or unsuitable for certain species or locations. Environmental DNA (eDNA) metabarcoding provides a non-invasive and relatively cheap alternative to explore patterns of diversity. It is important to recognize that, eDNA-based inference can vary across sampling methods, potentially impacting the validity of biodiversity assessments. To evaluate and compare the effectiveness of three eDNA sampling methods—ship-bottom intake (4.5 m), Niskin bottles (5 or 10 m), and bucket (0 m)—for assessing fish diversity and fish community composition in the western North Pacific near Japan, we analyzed fish communities from 83 stations sampled during nine research cruises. Taxonomic analysis revealed that each method detected over 324 taxa, contributing to a total of 465 taxa. Hierarchical clustering generally identified similar species composition across methods at a station. The exception was when intake samples, collected at different times, diverged from bucket and Niskin samples at the same station. Hill’s number rarefaction and extrapolation curves across all clusters showed similar results among methods, with exceptions in a few clusters where bucket samples exhibited higher biodiversity indices than intake and Niskin samples. Non-metric multidimensional scaling indicated significant relationships between cluster composition and environmental factors like temperature, salinity, and chlorophyll-a. Some clusters were also controlled by integrated seasonal factors. Overall, fish community composition was convincingly similar among methods. This finding suggests that any of these eDNA sampling methods can be effective and may be prioritized based on logistical considerations.

Environmental DNA of small pelagic fish in the deep ocean - Zeshu Yu; Marty Kwok-Shing Wong; Jun Inoue; Yuan Lin; Itsuka Yabe; Tomihiko Higuchi; Susumu Hyodo; Sachihiko Itoh; Yuichiro Nishibe; Hajime Obata; Shin-ichi Ito (Progress in Oceanography, 2026)

Association between deletions in the preS1/2 region of the hepatitis B virus genome and persistently abnormal ALT levels in patients with chronic hepatitis B treated with nucleos(t)ide analogs - Yurina Sato; Kotaro Doi; Jun Inoue; Masashi Ninomiya; Mio Tsuruoka; Kosuke Sato; Masazumi Onuki; Satoko Sawahashi; Keishi Ouchi; Kengo Watanabe; Hirofumi Niitsuma; Atsushi Masamune (Archives of Virology, 2026)
Patients with chronic hepatitis B (CHB) are at risk of developing hepatocellular carcinoma (HCC) during treatment with nucleos(t)ide analogs (NAs). Several factors, including abnormal ALT levels during NA treatment, are associated with HCC risk; however, the mechanisms of ALT abnormalities remain unknown. Here, deletions in the preS1/2 region of the hepatitis B virus (HBV) genome were evaluated in the context of persistent ALT abnormalities after NA treatment. Out of the 198 patients with CHB who had been treated with NAs, 40 who had been treated with entecavir, tenofovir disoproxil fumarate, or tenofovir alafenamide fumarate as the first-line therapy and from whom serum samples had been collected before NA treatment were selected for analysis of the infecting virus. Total DNA was extracted from the samples and subjected to nested PCR to detect deletions in the preS1/2 region of the HBV genome. Patients for whom deletions were found in ≥ 40% of the amplicons were classified as the "high-del" group, and the others were the "low-del" group. The preS1/2 region was amplified from 39 (97.5%) of the 40 samples, and a deletion was found in 19 of these patients (48.7%). The cumulative incidence of HCC was found to be significantly higher in the high-del group than in the low-del group (25% vs. 7% at 2 years, P = 0.021). The high-del group also had significantly higher ALT levels than the low-del group after 1 year of NA treatment (35 vs. 26 U/L, P = 0.020). In summary, patients with CHB with frequent preS1/2 deletions showed higher ALT levels after NA treatment and a higher risk of developing HCC.

Fish species detection by environmental DNA metabarcoding by three surface sampling methods - Sk Istiaque Ahmed; Zeshu Yu; Tomihiko Higuchi; Jun Inoue; Marty Kwok-Shing Wong; Susumu Yoshizawa; Sachihiko Itoh; Kosei Komatsu; Yusuke Kawaguchi; Eisuke Tsutsumi; Yuan Lin; Susumu Hyodo; et al. (Regional Studies in Marine Science, 2025)

Genetic evidence reveals that two wild boar (Sus scrofa) lineages invaded an island in Japan by swimming - Shintaro Ishizuka; Eiji Inoue; Takeo Kuriyama; Jun J. Sato (European Journal of Wildlife Research, 2025)

Terminal pleistocene organic carbon anomaly in Lake Biwa sediments linked to potential anthropogenic fires: Implications for early human impact on large lake systems - Jun Inoue; Toko Tanaka; Maiko Ikegami (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effects of kaempferol on weather-related pain: an open-label pilot study of subjective headache and other discomforts in pre-intervention and intervention periods in Japan - Yasutaka Ikeda; Moe Yamamoto; Aina Gotoh-Katoh; Shoichiro Inoue; Jun Sato (International Journal of Biometeorology, 2025)
Adverse or fluctuating weather conditions can negatively affect health, causing symptoms known as weather-related pain. Although pharmacological treatments, including painkillers, are commonly used, they frequently provide only symptomatic relief and may cause side effects. Therefore, interest in non-pharmacological and dietary interventions is increasing. While inner ear sensitivity to barometric pressure fluctuations—activating the sympathetic nervous system—has traditionally been considered the main mechanism, we propose that reduced oxygen utilization due to peripheral hypoxia under low barometric pressure is also a key factor. Kaempferol, a dietary flavonoid, has been shown in prior studies to enhance oxygen utilization and promote parasympathetic nervous system dominance. We hypothesized that daily kaempferol intake would alleviate weather-related discomfort by improving oxygen use and autonomic balance. In this pilot study, 458 individuals with moderate weather-related symptoms took 10 mg of kaempferol daily for 4 weeks. Participants completed questionnaires before and after the intervention. Data from 387 individuals with over 80% adherence were analyzed. Results showed significant reductions in symptom frequency (e.g., headache: Cohen’s d = 0.61, p < 0.001), duration (rank-biserial correlation = 0.64, p < 0.001), and severity (Cohen’s d = 0.57, p < 0.001). By the end of the intervention, over 80% of participants reported symptom improvement. These findings suggest that kaempferol is a promising non-pharmacological strategy for managing weather-related physical and mental symptoms by targeting oxygen utilization and autonomic regulation. This trial is registered with the UMIN Clinical Trials Registry (UMIN000045066).

Changes in the coastal environments and their impact on society in the Qaanaaq region, northwestern Greenland - Shin Sugiyama; Atsushi Yamaguchi; Tatsuya Watanabe; Yasumasa Tojo; Naotaka Hayashi; Jean-Baptiste Thiebot; Makoto Tomiyasu; Kohei Hasegawa; Yoko Mitani; Mayuko Otsuki; Yuta Sakuragi; Monica Ogawa; et al. (Polar Science, 2025)

From the plate to the brain: associations between dietary patterns and reduced dementia prevalence and white matter lesions in older Japanese adults - Liying Chen; Yasuko Tatewaki; Benjamin Thyreau; Kazuhiro Uchida; Hikari Iki; Shigeyuki Nakaji; Tetsuya Maeda; Kenjiro Ono; Moeko Noguchi-Shinohara; Masaru Mimura; Kenji Nakashima; Jun-ichi Iga; et al. (GeroScience, 2025)
Diet is widely considered essential in dementia, but its association with white matter lesions (WMLs) remains unclear. This cross-sectional study investigated the associations between dietary patterns, dementia, and WMLs in a large, nationwide, multicenter population of older Japanese adults. A total of 8,938 adults (aged ≥ 65; 73 ± 6.3 years old) from the Japan Prospective Studies Collaboration for Aging and Dementia (JPSC-AD) were included. Dietary intake was assessed using a Food Frequency Questionnaire. Principal component analysis was used to derive dietary patterns. A trained Convolutional Neural Network model segmented WMLs from brain MR images. Logistic regression estimated odds ratios (ORs) for dementia by dietary pattern quartiles, while linear regression assessed associations with WML volumes. Five dietary patterns were extracted. A Japanese diet including protein and minerals was significantly associated with lower prevalence of all-cause dementia (OR = 0.56) and Alzheimer’s disease (OR = 0.47), and with reduced WML volume ( β = − 0.03). Similar directional trends in ORs were observed across study sites. The reverse association with WMLs remained significant among individuals without dementia, reducing the likelihood of reverse causation. A Japanese diet including protein and minerals was associated with lower dementia prevalence and smaller WML volume in older Japanese adults. Drawing on nationwide, large-scale, multicenter data, these findings advance our understanding of dietary patterns in older Japanese adults and provide valuable insights for future intervention studies targeting diet and age-related brain changes.

Distribution of evergreen broad-leaved forests, inferred from phytolith, in the southernmost area of the Japanese Archipelago between the terminal Pleistocene and early Holocene - Naoki Hayashi; Jun Inoue (Quaternary International, 2025)

Impact of Canadian wildfires on aerosol and ice clouds in the early-autumn Arctic - Kazutoshi Sato; Kazu Takahashi; Jun Inoue (Atmospheric Research, 2025)

Sex Pheromone of the Azalea Mealybug: Absolute Configuration and Kairomonal Activity - Yuma Sugawara; Hiromitsu Inoue; Satoshi Toda; Jun Tabata (Journal of Chemical Ecology, 2024)

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Degranulation and expression of cytokines were modulated by diazinon in activated mast cells - Tomoko Ohdachi; Miyoko Matsushima; Moeko Ohara; Hina Kawashima; Goki Inoue; Kazuko Atsumi; Yuka Tsubosaki; Masahiro Takekoshi; Jun Ueyama; Naozumi Hashimoto; Mitsuo Sato; Yoshinori Hasegawa; et al. (Toxicology, 2024)

Polyandry may mitigate the negative impact of reproductive interference among bumblebees in Japan - Fumina Inokuchi; Maki N. Inoue; Yuya Kanbe; Masaaki Ito; Jun-ichi Takahashi; Tetsuro Nomura; Koichi Goka; Koji Tsuchida (The Science of Nature, 2024)
In social hymenopterans, monandry of the queen is an ancestral trait, and polyandry is a derived trait. Polyandry of the queen is the norm in a limited number of lineages, such as honeybees, leaf-cutting ants, Pogonomyrmex ants, and Vespula wasps, which presumably provide fitness advantages for the whole colony. The queen of the introduced bumblebee, Bombus terrestris , is polyandrous in Japan, whereas it is monandrous in native regions. We hypothesize that polyandry can evolve in a process that avoids the negative impacts of reproductive interference caused by interspecific mating and conducted genetic studies of the invasive species B. terrestris and two native subspecies, Bombus hypocrita sapporoensis and Bombus hypocrita hypocrita , in Japan. Our results revealed that although the native queens of B. hypocrita hypocrita allopatric with B. terrestris were strictly monandrous, the native queens of B. hypocrita sapporoensis sympatric with B. terrestris were polyandrous. These results suggested that the queens of native B. hypocrita sapporoensis do not experience negative impacts on interspecific mating from the invasive B. terrestris . We discuss the possibility that reproductive interference is a driving force in selection for multiple mating through an arms race between sympatric species.

Diversity and biogeography of dinoflagellates in the Kuroshio region revealed by 18S rRNA metabarcoding - Yubei Wu; Junya Hirai; Fanyu Zhou; Mitsunori Iwataki; Siyu Jiang; Hiroshi Ogawa; Jun Inoue; Susumu Hyodo; Hiroaki Saito (Frontiers in Marine Science, 2024)
Dinoflagellate is one of the most diverse and pervasive protists and a fundamental player in the marine food web dynamics and biogeochemical cycles. While possessing different nutritional strategies from purely autotrophy or heterotrophy to mixotrophy, some of them are also known as toxic harmful algal bloom (HAB) formers over the world. Despite their ordinariness, their diversity and biogeography are understudied in the open ocean compared with coastal region. As the first metabarcoding survey covering the Kuroshio current region from the offshore of Okinawa to the south of Honshu, we investigated the distribution of free-living dinoflagellates using the hypervariable V4 and V9 regions on 18S rRNA and their relation to ambient environments influenced by this oligotrophic but highly productive current in the northwest Pacific Ocean. We observed community structures differentiated by depth and nutrient concentrations. Most species annotated are autotrophic or mixotrophic and had a distribution correlated to warmer surface water, whereas heterotrophic species correlated to high nutrient levels or deeper layer. Our results also confirmed the overall high genetic diversity of dinoflagellates that decreased with depth and onshore. Most species present at stations offshore, and the relative abundance of HAB assemblages was lower at nutrient-rich stations on the continental shelf than stations influenced by the Kuroshio current, exhibiting the role of the Kuroshio transporting dinoflagellates including HAB species. To fully understand the dynamics of dinoflagellate communities in marine ecosystems, further seasonal monitoring is foremost for correlating dinoflagellates and environmental factors while completing the reference genomic database.

Challenges in Detecting Clouds in Polar Regions Using a Drone with Onboard Low-Cost Particle Counter - Jun Inoue; Kazutoshi Sato (Atmospheric Environment, 2023)

Bayesian network highlights the contributing factors for efficient arsenic phytoextraction by Pteris vittata in a contaminated field - Hiroshi Kudo; Ning Han; Daiki Yokoyama; Tomoko Matsumoto; Mei-Fang Chien; Jun Kikuchi; Chihiro Inoue (Science of The Total Environment, 2023)

The DiSCPersal model: A simple model for the small-scale atmospheric transport of spheroidal carbonaceous particles (SCPs) - Richard S. Vachula; Ann Sullivan Ojeda; Emma D. Henderson; Jun Inoue (Chemosphere, 2023)

Direct effect of orbital-insolation variation on long-term wildfire activity in central Japan demonstrated using a fuel moisture model - Jun Inoue; Kanta Sunada (Modeling Earth Systems and Environment, 2023)

Environmental DNA in the Kuroshio reveals environment-dependent distribution of economically important small pelagic fish - Zeshu Yu; Marty Kwok-Shing Wong; Jun Inoue; Sk Istiaque Ahmed; Tomihiko Higuchi; Susumu Hyodo; Sachihiko Itoh; Kosei Komatsu; Hiroaki Saito; Shin-ichi Ito (Frontiers in Marine Science, 2023)
Introduction Small pelagic fishes constitute large proportions of fisheries and are important components linking lower and higher trophic levels in marine ecosystems. Many small pelagic fishes in the Northwest Pacific spawn upstream in the Kuroshio and spend their juvenile stage in the Kuroshio Front area, indicating that the Kuroshio Current system impacts their stock fluctuations. However, the distribution of these fish relative to the Kuroshio has not been determined due to dynamic spatio-temporal fluctuations of the system. Here, the recent development of environmental DNA (eDNA) monitoring enabled us to investigate the distribution patterns of four economically important small pelagic fishes (Japanese sardine Sardinops melanostictus , Japanese anchovy Engraulis japonicus , chub mackerel Scomber japonicus, and blue mackerel Scomber australasicus ) in the Kuroshio Current system. Methods The influence of environmental factors, such as sea water temperature, salinity, oxygen concentration, chlorophyll-a concentration, and prey fish on the occurrence and quantity of target fish eDNA was analyzed using generalized additive models. In addition, the detection (presence) of target fish eDNA were compared between the offshore and inshore side areas of the Kuroshio axis. Results Sea water temperature showed important effect, especially on the distribution of Japanese sardine and Japanese anchovy, whereas the distribution pattern of chub mackerel and blue mackerel was greatly influenced by the eDNA quantity of Japanese sardine and Japanese anchovy (especially potential prey fish: Japanese anchovy). In addition, we found that the four target fish species could be observed in areas on the inshore side or around the Kuroshio axis, while they were hardly found on the offshore side. Conclusion Based on eDNA data, we succeeded in revealing detailed spatial distribution patterns of small pelagic fishes in the Kuroshio Current system and hypothesized predator–prey relationships influence their distribution in small pelagic fish communities.

Comparison of the depolarization measurement capability of a lidar ceilometer with cloud particle sensor sondes: A case study of liquid water clouds - Jun Inoue; Kazutoshi Sato (Polar Science, 2023)

Incorporative mixing in microreactors: Influence on reactions and importance of inlet designation - Shusaku Asano; Taisuke Maki; Shogo Inoue; Sumito Sogo; Masashi Furuta; Satoshi Watanabe; Yosuke Muranaka; Shinji Kudo; Jun-ichiro Hayashi; Kazuhiro Mae (Chemical Engineering Journal, 2023)

Vertical Profiles of 226Ra and 228Ra Activity Concentrations in the Western Subarctic Gyre of the Pacific Ocean - Hirofumi Tazoe; Hajime Obata; Takuya Hara; Mutsuo Inoue; Takahiro Tanaka; Jun Nishioka (Frontiers in Marine Science, 2022)
The vertical activity concentration distributions of the radium isotopes, 226 Ra and 228 Ra, which are useful as radiotracers, were obtained for the first time in the western Subarctic Pacific Gyre (WSAG). It was possible to detect short-lived 228 Ra present from the surface to 400 m depth by analyzing large seawater samples. Low 228 Ra and high 226 Ra activity concentrations in the surface layer in the WSAG were strongly influenced by upwelled deeper water with nutrients. The activity concentration distribution of 226 Ra especially was in good agreement with the silicate concentration distribution, which was consistent with previous reported findings. These distributions were uniform from the surface to 100 m of the dichothermal layer due to vertical mixing in winter. 228 Ra activity concentration decreased with water depth below the pycnocline and reached the undetectable level at 600 m which was within the oxygen minimum layer. Estimations of vertical fluxes of 228 Ra and nitrate according to 228 Ra decay indicated that the vertical transport by eddy diffusion was a minor process for the 228 Ra and nitrate fluxes, and lateral transport mainly affected 228 Ra in the intermediate warm water, that is, the mesothermal layer below the main pycnocline. Vertical mixing or submarine underground water and lateral transport to the WSAG could yield this 228 Ra in the intermediate depth.

Two Hidden mtDNA-Clades of Crown-of-Thorns Starfish in the Pacific Ocean - Nina Yasuda; Jun Inoue; Michael R. Hall; Manoj R. Nair; Mehdi Adjeroud; Miguel D. Fortes; Mutsumi Nishida; Nat Tuivavalagi; Rachel Ravago-Gotanco; Zac H. Forsman; Taha Soliman; Ryo Koyanagi; et al. (Frontiers in Marine Science, 2022)
Recurring outbreaks of crown-of-thorns starfish (COTS) severely damage healthy corals, especially in the Western Pacific Ocean. To obtain a better understanding of population genetics of COTS and historical colonization across the Pacific Ocean, complete mitochondrial genomes were sequenced from 243 individuals collected in 11 reef regions. Our results indicate that Pacific COTS ( Acanthaster cf. solaris ) comprise two major clades, an East-Central Pacific (ECP) clade and a Pan-Pacific (PP) clade, separation of which was supported by high bootstrap value. The ECP clade consists of COTS from French Polynesia, Fiji, Vanuatu and the Great Barrier Reef (GBR). The Hawaii population is unique within this clade, while California COTS are included in EPC clade. On the other hand, the PP clade comprises multiple lineages that contain COTS from Vietnam, the Philippines, Japan, Papua New Guinea, Micronesia, the Marshall Islands, GBR, Vanuatu, Fiji and French Polynesia. For example, a lineage of the PP clade, which has the largest geographic distribution, includes COTS from all of these locations. These results suggest two alternative histories of current geographic distributions of COTS in the Pacific Ocean, an ECP clade ancestry or Western Pacific clade ancestry. Although further questions remain to be explored, this discovery provides an evolutionary context for the interpretation of COTS population structure which will aid future coral reef research in the Pacific Ocean, and ultimately improve reef management of COTS.

Novel Mitochondrial DNA Markers for Scleractinian Corals and Generic-Level Environmental DNA Metabarcoding - Chuya Shinzato; Haruhi Narisoko; Koki Nishitsuji; Tomofumi Nagata; Noriyuki Satoh; Jun Inoue (Frontiers in Marine Science, 2021)
Coral reefs, the most biodiverse habitats in the ocean, are formed by anthozoan cnidarians, the scleractinian corals. Recently, however, ongoing climate change has imperiled scleractinian corals and coral reef environments are changing drastically. Thus, convenient, high-density monitoring of scleractinian corals is essential to understand changes in coral reef communities. Environmental DNA (eDNA) metabarcoding is potentially one of the most effective means of achieving it. Using publicly available scleractinian mitochondrial genomes, we developed high-specificity primers to amplify mitochondrial 12S ribosomal RNA (12S) and cytochrome oxidase-1 (CO1) genes of diverse scleractinian corals, which could be used for genus-level metabarcoding analyses, using next-generation sequencing technologies. To confirm the effectiveness of these primers, PCR amplicon sequencing was performed using eDNA isolated along the seashore of Okinawa, Japan. We successfully amplified all eDNA samples using PCR. Approximately 93 and 72% of PCR amplicon sequences of 12S and CO1 primers originated from scleractinian 12S and CO1 genes, respectively, confirming higher specificities for coral mitochondrial genes than primers previously used for coral eDNA metabarcoding. We also found that hierarchical clustering, based on the percentage of mapped reads to each scleractinian genus, discriminates between sampling locations, suggesting that eDNA surveys are sufficiently powerful to reveal differences between coral communities separated by <1 km. We conclude that the method reported here is a powerful tool for conducting efficient eDNA surveys targeting scleractinian corals.

Freshwater in the Arctic Ocean 2010–2019 - Amy Solomon; Céline Heuzé; Benjamin Rabe; Sheldon Bacon; Laurent Bertino; Patrick Heimbach; Jun Inoue; Doroteaciro Iovino; Ruth Mottram; Xiangdong Zhang; Yevgeny Aksenov; Ronan McAdam; et al. (Ocean Science, 2021)
The Arctic climate system is rapidly transitioning into a new regime with a reduction in the extent of sea ice, enhanced mixing in the ocean and atmosphere, and thus enhanced coupling within the ocean–ice–atmosphere system; these physical changes are leading to ecosystem changes in the Arctic Ocean. In this review paper, we assess one of the critically important aspects of this new regime, the variability of Arctic freshwater, which plays a fundamental role in the Arctic climate system by impacting ocean stratification and sea ice formation or melt. Liquid and solid freshwater exports also affect the global climate system, notably by impacting the global ocean overturning circulation. We assess how freshwater budgets have changed relative to the 2000–2010 period. We include discussions of processes such as poleward atmospheric moisture transport, runoff from the Greenland Ice Sheet and Arctic glaciers, the role of snow on sea ice, and vertical redistribution. Notably, sea ice cover has become more seasonal and more mobile; the mass loss of the Greenland Ice Sheet increased in the 2010s (particularly in the western, northern, and southern regions) and imported warm, salty Atlantic waters have shoaled. During 2000–2010, the Arctic Oscillation and moisture transport into the Arctic are in-phase and have a positive trend. This cyclonic atmospheric circulation pattern forces reduced freshwater content on the Atlantic–Eurasian side of the Arctic Ocean and freshwater gains in the Beaufort Gyre. We show that the trend in Arctic freshwater content in the 2010s has stabilized relative to the 2000s, potentially due to an increased compensation between a freshening of the Beaufort Gyre and a reduction in freshwater in the rest of the Arctic Ocean. However, large inter-model spread across the ocean reanalyses and uncertainty in the observations used in this study prevent a definitive conclusion about the degree of this compensation.

Postglacial anthropogenic fires related to cultural changes in central Japan, inferred from sedimentary charcoal records spanning glacial–interglacial cycles - Jun Inoue; Chikako Okuyama; Ryoma Hayashi; Yoshio Inouchi (Journal of Quaternary Science, 2021)
We examined long‐term charcoal records spanning the glacial–interglacial cycles that are evident in two cores collected from Lake Biwa in central Japan. We found that the records of the two cores have a similar long‐term variation pattern of charcoal concentrations and abundant large charcoal fragments in postglacial sediments, which indicates that frequent fires occurred near the shores of Lake Biwa during the postglacial period. Analogous natural conditions in the early postglacial period and the early part of the last interglacial period strongly suggest that the frequent fires that occurred only during the postglacial period were anthropogenic. A comparison between the charcoal records of Lake Biwa sediments and the cultural changes and human populations in this district suggests that anthropogenic fires in this district were influenced by the lifestyle and culture of each era rather than by the populations. Humans tended to use more fire at the start of the settlement during the early Neolithic era in this region, in spite of the small population size.

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Effect of viral DNA methylation on expression of hepatitis B virus proteins depends on the virus genotype - Takuya Nakamura; Jun Inoue; Masashi Ninomiya; Eiji Kakazu; Tomoaki Iwata; Satoshi Takai; Akitoshi Sano; Takayuki Kogure; Tooru Shimosegawa; Atsushi Masamune (Virus Genes, 2020)

Antarctic Radiosonde Observations Reduce Uncertainties and Errors in Reanalyses and Forecasts over the Southern Ocean: An Extreme Cyclone Case - Kazutoshi Sato; Jun Inoue; Akira Yamazaki; Naohiko Hirasawa; Konosuke Sugiura; Kyohei Yamada (Advances in Atmospheric Sciences, 2020)
Cyclones with strong winds can make the Southern Ocean and the Antarctic a dangerous environment. Accurate weather forecasts are essential for safe shipping in the Southern Ocean and observational and logistical operations at Antarctic research stations. This study investigated the impact of additional radiosonde observations from Research Vessel “Shirase” over the Southern Ocean and Dome Fuji Station in Antarctica on reanalysis data and forecast experiments using an ensemble data assimilation system comprising the Atmospheric General Circulation Model for the Earth Simulator and the Local Ensemble Transform Kalman Filter Experimental Ensemble Reanalysis, version 2. A 63-member ensemble forecast experiment was conducted focusing on an unusually strong Antarctic cyclonic event. Reanalysis data with (observing system experiment) and without (control) additional radiosonde data were used as initial values. The observing system experiment correctly captured the central pressure of the cyclone, which led to the reliable prediction of the strong winds and moisture transport near the coast. Conversely, the control experiment predicted lower wind speeds because it failed to forecast the central pressure of the cyclone adequately. Differences were found in cyclone predictions of operational forecast systems with and without assimilation of radiosonde observations from Dome Fuji Station.

Predictability of storm wave heights in the ice-free Beaufort Sea - Takehiko Nose; Adrean Webb; Takuji Waseda; Jun Inoue; Kazutoshi Sato (Ocean Dynamics, 2018)

Development of a new benzodiazepine hypnotics withdrawal symptom scale - Mina Kobayashi; Isa Okajima; Hajime Narisawa; Takashi Kikuchi; Kentaro Matsui; Ken Inada; Jun Ishigooka; Yuichi Inoue (Sleep and Biological Rhythms, 2018)

Changes in phytoplankton community structure during wind-induced fall bloom on the central Chukchi shelf - Amane Fujiwara; Shigeto Nishino; Kohei Matsuno; Jonaotaro Onodera; Yusuke Kawaguchi; Toru Hirawake; Koji Suzuki; Jun Inoue; Takashi Kikuchi (Polar Biology, 2018)

Comparison of Arctic sea ice thickness and snow depth estimates from CFSR with in situ observations - Kazutoshi Sato; Jun Inoue (Climate Dynamics, 2018)

Coupled Response of Bacterial Production to a Wind-Induced Fall Phytoplankton Bloom and Sediment Resuspension in the Chukchi Sea Shelf, Western Arctic Ocean - Mario Uchimiya; Chiaki Motegi; Shigeto Nishino; Yusuke Kawaguchi; Jun Inoue; Hiroshi Ogawa; Toshi Nagata (Frontiers in Marine Science, 2016)

A correlation of reactive oxygen species accumulation by depletion of superoxide dismutases with age-dependent impairment in the nervous system and muscles of Drosophila adults - Saori Oka; Jun Hirai; Takashi Yasukawa; Yasuyuki Nakahara; Yoshihiro H. Inoue (Biogerontology, 2015)

Reproductive success of Pacific copepods in the Arctic Ocean and the possibility of changes in the Arctic ecosystem - Kohei Matsuno; Atsushi Yamaguchi; Toru Hirawake; Shigeto Nishino; Jun Inoue; Takashi Kikuchi (Polar Biology, 2015)

Simultaneous determination of water-soluble vitamins in beverages and dietary supplements by LC-MS/MS - Ayano Kakitani; Tomonori Inoue; Keiko Matsumoto; Jun Watanabe; Yasushi Nagatomi; Naoki Mochizuki (Food Additives & Contaminants: Part A, 2014)

The review of innovative integration of Kampo medicine and Western medicine as personalized medicine at the first multidisciplinary pain center in Japan - Young-Chang P Arai; Hiromichi Yasui; Hideya Isai; Takashi Kawai; Makoto Nishihara; Jun Sato; Tatsunori Ikemoto; Sinsuke Inoue; Takahiro Ushida (EPMA Journal, 2014)

Rhynchophylline-induced vasodilation in human mesenteric artery is mainly due to blockage of L-type calcium channels in vascular smooth muscle cells - Peng-Yun Li; Xiao-Rong Zeng; Jun Cheng; Jing Wen; Isao Inoue; Yan Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Nerve growth factor-induced endocytosis of TWIK-related acid-sensitive K+ 1 channels in adrenal medullary cells and PC12 cells - Hidetada Matsuoka; Keita Harada; Jun Nakamura; Masumi Inoue (Pflügers Archiv - European Journal of Physiology, 2013)

The Use of Size Distributions of Spheroidal Carbonaceous Particles in Swimming Pool Deposits for Evaluating Atmospheric Particle Behaviour - Jun Inoue; Arisa Tomozawa; Takamoto Okudaira (Water, Air, & Soil Pollution, 2013)

Down-regulation of miR-124/-214 in cutaneous squamous cell carcinoma mediates abnormal cell proliferation via the induction of ERK - Keitaro Yamane; Masatoshi Jinnin; Tomomi Etoh; Yuki Kobayashi; Naoki Shimozono; Satoshi Fukushima; Shinichi Masuguchi; Keishi Maruo; Yuji Inoue; Tsuyoshi Ishihara; Jun Aoi; Yuichi Oike; et al. (Journal of Molecular Medicine, 2013)

Efficient establishment of primary fibroblast cultures from the hawksbill sea turtle (Eretmochelys imbricata) - Tomokazu Fukuda; Jun Kurita; Tomomi Saito; Kei Yuasa; Masanobu Kurita; Kenichiro Donai; Hiroshi Nitto; Makoto Soichi; Katsuhiko Nishimori; Takafumi Uchida; Emiko Isogai; Manabu Onuma; et al. (In Vitro Cellular & Developmental Biology - Animal, 2012)

Characteristic Differences in the Chemical Composition of Spheroidal Carbonaceous Particles in Japanese and Chinese Cities - Azusa Momose; Jun Inoue; Akiko Murakami-Kitase; Takamoto Okudaira; Shusaku Yoshikawa (Water, Air, & Soil Pollution, 2012)

Differential distribution of synaptotagmin-1, -4, -7, and -9 in rat adrenal chromaffin cells - Hidetada Matsuoka; Keita Harada; Jun Nakamura; Mitsunori Fukuda; Masumi Inoue (Cell and Tissue Research, 2011)

A multiple-isotope (δ37Cl, 14C, 3H) approach to reveal the coastal hydrogeological system and its temporal changes in western Kyushu, Japan - Tomochika Tokunaga; Jun Shimada; Yuki Kimura; Daisuke Inoue; Katsuro Mogi; Kazumi Asai (Hydrogeology Journal, 2011)

Enhanced expression of human cDNA by phosphoglycerate kinase promoter-puromycin cassette in the mouse transthyretin locus - Zhenghua Li; Gang Zhao; Jingling Shen; Kimi Araki; Kyoko Haruna; Seiya Inoue; Jun Wang; Ken-ichi Yamamura (Transgenic Research, 2011)

Comparison of urinary concentrations of 3-phenoxybenzoic acid among general residents in rural and suburban areas and employees of pest control firms - Akiko Kimata; Takaaki Kondo; Jun Ueyama; Kanami Yamamoto; Junko Yoshitake; Kenji Takagi; Koji Suzuki; Takashi Inoue; Yoshinori Ito; Nobuyuki Hamajima; Michiro Kamijima; Masahiro Gotoh; et al. (International Archives of Occupational and Environmental Health, 2009)

Benzene activates caspase-4 and -12 at the transcription level, without an association with apoptosis, in mouse bone marrow cells lacking the p53 gene - Jung-Yeon Yi; Yoko Hirabayashi; Yang-Kyu Choi; Yukio Kodama; Jun Kanno; Jeong-Hee Han; Tohru Inoue; Byung-Il Yoon (Archives of Toxicology, 2009)

Limited lactational transfer of acrylamide to rat offspring on maternal oral administration during the gestation and lactation periods - Miwa Takahashi; Makoto Shibutani; Jun Nakahigashi; Natsumi Sakaguchi; Kaoru Inoue; Tomomi Morikawa; Midori Yoshida; Akiyoshi Nishikawa (Archives of Toxicology, 2009)

Functional Polymorphism of the Human Multidrug Resistance Gene (MDR1) and Polydipsia–Hyponatremia in Schizophrenia - Takahiro Shinkai; Vincenzo De Luca; Kensuke Utsunomiya; Shinichi Sakata; Yoshiaki Inoue; Yuko Fukunaka; Rudi Hwang; Osamu Ohmori; James L. Kennedy; Jun Nakamura (NeuroMolecular Medicine, 2008)

In situ strength measurements on natural upper-mantle minerals - Junji Yamamoto; Jun-ichi Ando; Hiroyuki Kagi; Toru Inoue; Akihiro Yamada; Daisuke Yamazaki; Tetsuo Irifune (Physics and Chemistry of Minerals, 2008)

Displacement of Japanese native bumblebees by the recently introduced Bombus terrestris (L.) (Hymenoptera: Apidae) - Maki N. Inoue; Jun Yokoyama; Izumi Washitani (Journal of Insect Conservation, 2008)

Detection of viruses associated with rugose wood in Japanese grapevines and analysis of genomic variability of Rupestris stem pitting-associated virus - Ryoji Nakaune; Koji Inoue; Hideo Nasu; Katsura Kakogawa; Hiromichi Nitta; Jun Imada; Masaaki Nakano (Journal of General Plant Pathology, 2008)

Membrane Channel Connexin 32 Maintains Lin−/c-kit+ Hematopoietic Progenitor Cell Compartment: Analysis of the Cell Cycle - Yoko Hirabayashi; Byung-Il Yoon; Isao Tsuboi; Yan Huo; Yukio Kodama; Jun Kanno; Thomas Ott; James E. Trosko; Tohru Inoue (The Journal of Membrane Biology, 2007)

Adsorption of OP1-related bacteriophages requires the gene encoding a TonB-dependent receptor-like protein in Xanthomonas oryzae pv. oryzae - Yasuhiro Inoue; Seiji Tsuge; Jun Ohnishi; Takayuki Matsuura; Hirokazu Ochiai; Hisatoshi Kaku; Koji Azegami (Journal of General Plant Pathology, 2007)

Evaluation of snow/ice albedo parameterizations and their impacts on sea ice simulations - Jiping Liu; Zhanhai Zhang; Jun Inoue; Radley M. Horton (International Journal of Climatology, 2007)
Climate models use a variety of snow/ice albedo parameterizations for the ice covered ocean. In this study, we applied in situ measurements (surface temperature, snow depth and ice thickness) obtained from the Surface Heat Budget of the Arctic Ocean (SHEBA) as input values to four different snow/ice albedo parameterizations (representing the spectrum of parameterizations used in stand‐alone sea ice models, numerical weather prediction and regional climate models of the Arctic Basin, and coupled global climate models), and evaluated the parameterized albedos against the SHEBA observed albedo. Results show that these parameterizations give very different representations of surface albedo. The impacts of systematic biases in the input values on the parameterized albedos were also assessed. To further understand how sea ice processes are influenced by differences in the albedo parameterizations, we examined baseline sea ice characteristics and responses of sea ice to an external perturbation for the simulations of the albedo parameterizations using a stand‐alone basin‐scale dynamic/thermodynamic sea ice model. Results show that an albedo treatment of sufficient complexity can produce more realistic basin‐scale ice distributions, and likely more realistic ice responses as climate warms. Copyright © 2006 Royal Meteorological Society

Effects of repeated milnacipran administration on brain serotonergic and noradrenergic functions in healthy volunteers - Atsushi Soya; Takeshi Terao; Mami Nakajima; Hideki Kojima; Tatsuya Okamoto; Yoshiaki Inoue; Miki Iwakawa; Koji Shinkai; Reiji Yoshimura; Yoichi Ueta; Jun Nakamura (Psychopharmacology, 2006)

Mechanism of the olivine–ringwoodite transformation in the presence of aqueous fluid - Jun-ichi Ando; Naotaka Tomioka; Kazunari Matsubara; Toru Inoue; Tetsuo Irifune (Physics and Chemistry of Minerals, 2006)

‘Evolution of a Storm-driven Cloudy Boundary Layer in the Arctic’ - Jun Inoue; Branko Kosović; Judith A. Curry (Boundary-Layer Meteorology, 2005)

Aircraft Observations of Air-mass Modification Over the Sea of Okhotsk during Sea-ice Growth - Jun Inoue; Masayuki Kawashima; Yasushi Fujiyoshi; Masaaki Wakatsuchi (Boundary-Layer Meteorology, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

Impact of biological clogging agents on filter and emitter discharge characteristics of microirrigation systems - Hossein DehghaniSanij; Tahei Yamamoto; Velu Rasiah; Jun Utsunomiya; Mitsuhiro Inoue (Irrigation and Drainage, 2004)
Water application efficiency of microirrigation systems (MIS) may depend, at least partially, on algae and protozoa (biological clogging agents, BCAs) induced filter and emitter clogging. In this study we assessed the impact of BCA‐induced changes on water discharge rate and distribution uniformity from (i) emitters with different water flow cross‐section (CS) area, pressure compensation (PC) systems, and inbuilt filtration areas (FAs), and (ii) filters either made of urethane, sand, or disk in the Tohaku irrigation project in Japan. In a field experiment, four types of on‐line emitters on each of four laterals and four types of in‐line emitters on each of another four laterals were assessed for BCA‐induced emitter discharge performance without using filters in the field irrigation line. The emitters' discharge rate increased with increasing CS, FA, and working pressure (WP) and decreased when the emitters were on‐line in the laterals and with increasing BCA counts. Because BCAs are the only dynamic variable in the above relationship, we conclude that BCA‐induced clogging is a major issue when filters were not installed in field irrigation lines. The filter performance assessment based on the number of backwashings required to restore the working pressure to the recommended level indicated that BCA filtering by the sand filter was highest, followed by disk and urethane, respectively. Copyright © 2004 John Wiley & Sons, Ltd.

Ecological Aspects of the Downstream Migration of Introduced European Eels in the Uono River, Japan - Takeshi Miyai; Jun Aoyama; Seji Sasai; Jun G. Inoue; Michael J. Miller; Katsumi Tsukamoto (Environmental Biology of Fishes, 2004)

Development and implementation of a database system to manage a large-scale mouse ENU-mutagenesis program - Hiroshi Masuya; Yuji Nakai; Hiromi Motegi; Norio Niinaya; Yuichiro Kida; Yoshiharu Kaneko; Haruhiko Aritake; Nobuaki Suzuki; Jun Ishii; Koji Koorikawa; Tomohiro Suzuki; Maki Inoue; et al. (Mammalian Genome, 2004)

Seasonal and secular variations of sunshine duration and natural seasons in Japan - Tomoshige Inoue; Jun Matsumoto (International Journal of Climatology, 2003)
Seasonal transitions of sunshine duration and their secular changes in Japan are investigated for the period 1951–2000, and the influence of climatic variations on seasonal weather tendencies is discussed. Two seasons with little sunshine in the Baiu and the Akisame seasons are recognized in central and western Japan (CW Japan). In northern Japan, however, only one season with little sunshine in summer is seen. Another season with little sunshine is recognized for the Sea of Japan side and the Southwest Islands during the winter monsoon season. The sunshine duration from spring to autumn in northern Japan decreased in the late 1980s and the 1990s, and the period of little sunshine in summer has become longer since the mid 1980s. In CW Japan, sunshine in late spring in the 1950s and the early 1960s was less than that in other years. A rapid increase in sunshine duration which corresponds with the end of the Baiu rainy season has been delayed since 1980. The period in midsummer with little sunshine has also appeared more frequently than it did before 1980. In the Southwest Islands, sunshine duration has been decreasing almost all through the year. When comparing the differences between the Sea of Japan side and the Pacific Ocean side in winter, the sunshine contrast between them has intensified recently. By using sunshine duration, an objective classification of six natural seasons in CW Japan is conducted. Then, the long‐term change of seasonal march in CW Japan is investigated. The end dates of the Baiu season after 1980 have been delayed by about 5 days compared with those before 1980. From the viewpoint of sunshine contrasts between the Sea of Japan side and the Pacific Ocean side, the winter monsoon season in Japan has become longer in recent years, even under the warming trend of winter temperature. Copyright © 2003 Royal Meteorological Society

Mitochondrial Genomics of Ostariophysan Fishes: Perspectives on Phylogeny and Biogeography - Kenji Saitoh; Masaki Miya; Jun G. Inoue; Naoya B. Ishiguro; Mutsumi Nishida (Journal of Molecular Evolution, 2003)

Molecular characterization and gene expression of lhcb5 gene encoding CP26 in the light-harvesting complex II of Chlamydomonas reinhardtii - Jun Minagawa; Kab-Cho Han; Naoshi Dohmae; Koji Takio; Yorinao Inoue (Plant Molecular Biology, 2001)

Wind Fields over Funka Bay and Their Effect on Water Circulation in the Bay - Jun Inoue; Masayuki Kawashima; Kay I. Ohshima; Yasushi Fujiyoshi; Ken-ichi Maruyama (Journal of Oceanography, 2000)

Characterization of chloroplast psbA transformants of Chlamydomonas reinhardtii with impaired processing of a precursor of a photosystem II reaction center protein, D1 - Aya Hatano-Iwasaki; Jun Minagawa; Yorinao Inoue; Yuichiro Takahashi (Plant Molecular Biology, 2000)